STaRT-RWE: structured template for planning and reporting on the implementation of real-world evidence studies - S. L. Plavinskij; A. N. Barinova (Реальная клиническая практика: данные и доказательства, 2022)
Aim. To highlight the features of STaRT-RWE (a structured template for planning and reporting on research in real clinical practice — RWE).Materials and methods. One has selected and analyzed of the articles, dealing with the special features of getting evidence under conditions of real clinical routine, simplification of proving data collecting, in particular, at simultaneous consideration of several researches RWE.Results. Due to the use of this pattern, one selects crucially important details. It is also important that the different interpretation does not influence the results and solvation.Conclusion. STaRT-RWE is meant for decreasing the incorrect interpretation and making clear expectations as for generating RWE if to speak about the research design and its details, how and where these data should be revealed which will allow the persons, taking part in healthcare, estimate the RWE research reliability in an effective way.